2017
DOI: 10.5530/pj.2017.4.81
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Antioxidant-Riched Dendrobium longicornu

Abstract: Context: Dendrobium longicornu is a traditional medicinal plant widely used in Asia. It has many bioactive compounds like bibenzyl, phenanthrenes, phenolic compounds. There has been little research in the cytotoxic and antioxidant effects of D. longicornu. Aims: The aim of this study was to investigate the cytotoxic and antioxidant activities of this plant. Settings and Design: Antioxidant and cytotoxic activity of Dendrobium longicornu extracts. Methods and Material: The plant extracts were prepared by soxhle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
(19 reference statements)
2
13
0
Order By: Relevance
“…In contrast, both chloroform and acetone extracts exhibited high TPC and TFC, probably because these extracts contain many compounds of polyphenol and flavonoid groups with polarities similar to those of chloroform and acetone. Previous research on the extraction of differing flavonoid and polyphenol contents and compounds in different solvents in various Dendrobium species supports the present research [ 37 , 41 44 ]. The types of compounds we identified in D. moniliforme in this study were similar to those identified in this plant in previous studies [ 10 – 15 ].…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, both chloroform and acetone extracts exhibited high TPC and TFC, probably because these extracts contain many compounds of polyphenol and flavonoid groups with polarities similar to those of chloroform and acetone. Previous research on the extraction of differing flavonoid and polyphenol contents and compounds in different solvents in various Dendrobium species supports the present research [ 37 , 41 44 ]. The types of compounds we identified in D. moniliforme in this study were similar to those identified in this plant in previous studies [ 10 – 15 ].…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that the methanol extract is more potent on the cell lines used. The antitumor and anticancer activities of crude extracts of Dendrobium were explained in previous studies (Devi et al 2009;Lam et al 2015;Shrestha et al 2015;Sun et al 2016;Paudel et al 2017). In our previous study, we quantified the total phenolic and flavonoid contents in the crude extract of D. amoenum (Paudel et al 2015).…”
Section: Discussionmentioning
confidence: 77%
“…Dendrobium longicornu exhibits the DPPH free radical scavenging capacity as it has many antioxidant-rich secondary metabolites [ [4] , [5] , [6] , [7] , 29 ]. We have already evaluated the antioxidant, cytotoxic and antimicrobial capacity of its wild counterparts [ 8 , 9 ]. Its secondary metabolites scavenged DPPH radicals that would be measured at 517 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The whole plant of D. longicornu largely contains bibenzyl and phenanthrene, as well as minimal amounts of monoaromatics, steroid and flavonoid derivatives [ [4] , [5] , [6] , [7] ]. Due to the presence of such compounds, its extract has been shown the antioxidant, antimicrobial and cytotoxic effects [ 8 , 9 ]. Its wild resource has been depleted by overexploitation to meet the demand in traditional medicine.…”
Section: Introductionmentioning
confidence: 99%